2004
DOI: 10.1159/000082189
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Therapeutic Effects of Once-Daily Molsidomine Used as an Add-On Treatment in Patients with Stable Angina pectoris

Abstract: Background: A once-daily 16-mg-dose formulation of molsidomine (Coruno® tablets) was recently developed for the chronic treatment of angina pectoris. It required efficacy and safety testing. Objective: The objective of the present study was to compare the efficacy and tolerability of Coruno with that of the currently prescribed twice-daily 8-mg dose of molsidomine (Corvatard® tablets), using them as add-on therapies in patients with stable angina pectoris aged either less or more than 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…This is in line with the results of a previous study, which showed that the induced clinical improvement with molsidomine 16 mg once daily was quantitatively larger in the more severely-in that case, elderlydisabled patients. 9,10 Compliance with molsidomine 16 mg once daily was overall excellent and quite similar in both cohorts. Incidences of AEs and drug-related AEs were not significantly different between Hungarian and Polish patients, nor between placebo and molsidomine.…”
Section: Discussionmentioning
confidence: 90%
“…This is in line with the results of a previous study, which showed that the induced clinical improvement with molsidomine 16 mg once daily was quantitatively larger in the more severely-in that case, elderlydisabled patients. 9,10 Compliance with molsidomine 16 mg once daily was overall excellent and quite similar in both cohorts. Incidences of AEs and drug-related AEs were not significantly different between Hungarian and Polish patients, nor between placebo and molsidomine.…”
Section: Discussionmentioning
confidence: 90%